Ameliorative activities of Malaysian stingless bee honey on lipopolysaccharide-induced inflammation and oxidative stress In vivo and its underlying mechanisms - Ranneh, Yazan (2018)
Inflammation and oxidative stress have been considered the major contributor in developing chronic diseases including cancer, atherosclerosis, diabetes, neurodegenerative diseases, arthritis and obesity. A number of dietary and nutraceuticals interventions to attenuate inflammation- and oxidative stress-related diseases target pro-inflammatory mediators, reactive oxygen species, transcription factors including nuclear factor-kappa B (NF-κB), and nuclear factor erythroid 2- releated factor 2 (Nrf-2) and specific regulatory transcription proteins including P38- mitogen activated protein kinases (P38-MAPK) and high mobility group box-1 protein (HMGB-1) and. Stingless bee honey (SBH) has been recently found to be rich in bioactive compounds especially, polyphenols more than honey-made by normal bee. The unique body size of stingless bee helps her stretch itself inside a plenty number of flowers which increase the diversity of collected polyphenols and preserve them from degradation. In this study, SBH had a higher phenolic content than other types of normal honey and there were fifteen phenolic compounds identified using LCMS/ MS. The richness of SBH in phenolic compounds were also manifested with high and significant total antioxidant capacity measured by DPPH, ABTS and ORAC assays. The significant statistical correlation between polyphenols content and antioxidant results confirmed the biological actions of SBH against free radicals. Subsequently, a model of chronic subclinical systemic inflammation was developed by injecting male rats with 1 mg/kg of lipopolysaccharide thrice per week for 28 days. The results demonstrated an elevation in C-reactive protein, IL-6, TNF-α and lymphocyte along with inflammatory changes in the histological features of heart, lung, kidney and liver tissues. Then, the ability of SBH to mitigate inflammation and oxidative stress was studied in two separate experiments; systemic acute inflammation and chronic subclinical systemic inflammation. In the first experiment, SBH was supplemented at two different doses (4.6 and 9.3 g/kg/day) for seven days prior to induce systemic acute inflammation by injecting male rat with 5 mg/kg LPS. In the second experiment, SBH was supplemented for 30 days at two different doses (4.6 and 9.3 g/kg/day) concurrently with 1 mg/kg of LPS injection thrice per week for 28 days to induce chronic subclinical systemic inflammation. In both experiments, SBH demonstrated a significant reduction in pro-inflammatory mediators and oxidative stress. Regulating the protein levels of NF-κB, p38-MAPK, HMGB-1 and activating Nrf-2 in SBH treated group unveiled partially the mechanism of SBH against inflammation and oxidative stress. The histopathological examination of both studies revealed that SBH exceled a reduction in the pathology of heart, lung, kidney and liver. These biological activates of SBH could be due to the synergistic actions of polyphenols and it also provides a novel insight into the possible mechanism behind the preventive actions of SBH on the emergence of inflammation and oxidative markers in rats with LPS-induced inflammation. Collectively, the results presented in this thesis suggest that SBH can mitigate and prevent systemic acute inflammation and chronic subclinical systemic inflammation along with oxidative stress via regulating NF-κB, P38-MAPK, HMGB-1 and Nrf-2. SBH is expected to be a useful natural supplement for alleviating and preventing oxidative stress and chronic inflammationrelated diseases.